Nyepi di Kampung Muslim Al-Amin: Leksikon Dinamika Sosial Toleransi Beragama di Denpasar, Bali - I Nengah Punia,; Ni Luh Nyoman Kebayantini,; Wahyu Budi Nugroho, (Jurnal Kajian Bali (Journal of Bali Studies), 2018)
This research examines the habitus creation in the neighborhood of Al-Amin which is located at Banjar Sanglah, Denpasar City. This neighborhood evidently is able to actualize the inter-religious harmony since 1970 until now. In the related study, the concept of habitus from Pierre Bourdieu with formulation (Habitus x Capital) + Field = Practice was applied, while adopted the ethnography method. Through the conducted study, Bourdieu’s concept of habitus was able to explain the cognitive structure of various actors who play an essential role in the creation of the Al-Amin neighborhood, starting from the system of symbolic capital disposition, social capital, economic capital and cultural capital. Furthermore, the continuous harmony in the neighborhood of Al-Amin is due to its strong social and cultural capital. However, the harmony is inseparable from the framework between majority with minority, thus the character of social capital and especially the cultural capital in the neighborhood of Al-Amin tend to coopt other forms of capital.
Keywords: Al-Amin; moslem village; habitus; harmony